Design of solar cell using mirror, cooling, double axis, and solar tracking - Yulianta Siregar; Mai Kai Suan Tial; Yopi Fernando Soarez Purba; Suherman Suherman; Soeharwinto Soeharwinto (Institute of Advanced Engineering and Science, 2022)
Fossil energy sources are dwindling. It is necessary to develop alternative energy sources for future energy. The solar cell is an alternative energy that can be used in Indonesia. The current challenge is utilizing solar panels for the best possible power production. This research gives the solution to design an increase in solar cell output power by using mirrors, cooling, and a double-axis solar tracking control system. The results show that using a mirror, cooling, and double-axis solar tracking produces optimal output power with a current and power are 2.43 amperes and 40.3 watts, respectively. Meanwhile, several factors can affect this solar panel's efficiency. Specifically, the amount of solar radiation that the solar panel can receive depends on the climate on the day and location of the research and the solar panel's dimensions.